Development of a rapid neutralization testing system for Rhinovirus C15 based on the enzyme-linked immunospot assay - Zhou, Zhenhong; Zhu, Rui; Yang, Hongwei; Xu, Longfa; Chen, Hao; Wu, Yuanyuan; Yin, Zhichao; Huang, Qiongzi; Zhang, Dongqing; Liu, Che; Que, Yuqiong; Zhang, Jun; et al. (Frontiers in Microbiology, 2022)
Human rhinoviruses (RVs) are dominant pathogens causing a wide range of respiratory tract diseases, posing a huge threat to public health worldwide. Viruses belonging to the RV-C species are more likely to cause severe illnesses and are strongly associated with asthma onset or exacerbations than RV-A or RV-B. Rapid and sensitive detection of neutralizing antibodies (NAbs) against RV-C can promote the development of vaccines and antiviral drugs and help in the diagnosis of viral infection. In this study, a rapid neutralization testing system for RV-C15, based on an enzyme-linked immunospot assay (Nt-ELISPOT) was developed. A monoclonal antibody (MAb), named 9F9, with high binding efficacy for RV-C15 conjugated to horseradish peroxidase (HRP), was used to detect RV-C15-infected cells at a concentration of 2 μg/mL. The optimal infectious dose of RV-C15 was set at 1 × 104 TCID50/well and the cells were fixed with 0.5% formaldehyde diluted in PBS after incubation for 20 h. Compared with the traditional cytopathic effect (CPE)-based neutralization assay (Nt-CPE), Nt-ELISPOT significantly shortened the detection period and showed good consistency with the detection of neutralizing titers of both sera and neutralizing antibodies. Using Nt-ELISPOT, three anti-RV-C15 NAbs were obtained with IC50 values of 0.16, 0.27, and 11.8 μg/mL, respectively. Moreover, 64 human serum samples collected from a wide range of age groups were tested for NAb against RV-C15 by Nt-ELISPOT. The total seroprevalence was 48.4% (31/64) and the positive rate was lowest in the group under 6 years old. Thus, the Nt-ELISPOT established in this study can be used as a high-throughput and rapid neutralization assay for the screening of NAbs and for seroepidemiological investigation against RV-C15.